'What happened next?': Developmental changes in mothers' questions to children. (December 2016) - Kuchirko, Yana; Tamis-LeMonda, Catherine S; Luo, Rufan; Liang, Eva
Developmental changes in the questions mothers asked during book-sharing interactions with their preschool children and associations between mothers' questions and children's narrative contributions were examined. Children and mothers from ethnically diverse backgrounds (African American, Dominican and Mexican) were video-recorded sharing the wordless book 'Frog, Where are You?' when children were three, four and five years of age. Mothers' questions were coded as referential (e.g. 'What's that?'), story-specific (e.g. 'Where is the boy looking for the frog?') and open-ended (e.g. 'What will happen next?'). Mothers decreased their use of referential questions between the child ages of four and five in both frequency and proportion. Story-specific questions increased in frequency and proportion with increasing child age. Open-ended questions decreased in frequency between the child ages of four and five and did not change in proportion over time. Mothers' question types related to children's narrative contributions concurrently and over time.